Pengaruh Kualitas Pelayanan Penyelenggaraan Sport Event Terhadap Kepuasan Peserta Jakarta Marathon 2020 - Rizky Adhy Satria Mulya (Politeknik Pariwisata NHI Bandung, 2022)
Sports tourism in this era has become a new paradigm and has received a lot of attention from stakeholders, such as the central and local governments, the private sector, academics to the community. Sports tourism has become a tourist trip to be able to play a role in sports activities (participants and committees), such as recreation, competiting and visit the sports venues, such as football stadiums. Jakarta Marathon or JakMar is an annual event held by PT. Inspiro MICE Promoter. In 2013, PT. Inspiro Promoter MICE was held the National and International Jakarta Marathon for the first time. The theory used in this research is the theory of service quality which consists of 3 aspects, such as Physical Environment Quality, Interaction Quality, and Outcome Quality by means of analysis based on descriptive statistics, IPA (Important Performance Analysis) analysis techniques, and multiple linear regression analysis. Results Based on the calculation of the gap between the perceptions and expectations of respondents, it was found that marathon participants were not satisfied with the service quality of organizing sporting events. Based on the results of the IPA in quadrant A (Main Priority which means Dissatisfied and Very Important) there are 2 indicators that must be the main priority for the implementation in improving services, while based on the coefficient test of Physical Environment Quality, Interaction Quality, and Outcome Quality, it affects the satisfaction achieved. given to marathon participants by 75.7% while the remaining 24.3% was influenced by other factors not observed in this study.